Rehabilitation Assessment and Treatment for Low Back Pain - YUE Shouwei (康复学报)
Low back pain (LBP) is a kind of clinical syndrome characterized by complex etiology, lifetime prevalence, the long course of disease and easy recurrence. If not treated in time, it will affect the quality of patient life and increase the social economic burden. This study summarized the disease classification, epidemiology, etiology (muscle strength decline, lumbar disc degeneration, facet joint degeneration, nerve root and dorsal root ganglion lesions), influencing factors, rehabilitation assessment (medical history collection, pain assessment, physical dysfunction test, imaging examination, clinical efficacy evaluation, etc.) and rehabilitation treatment [drug therapy, exercise therapy (trunk muscle training, core stability training/motor control, McKenzie therapy, Pilates exercise, water exercise, sling exercise training), manual therapy (mobilization of the spine, thoracic mobilization, myofascial release techniques), physical modalities, behavioral therapy, traditional Chinese medicine rehabilitation therapy (traditional Chinese medicine/Chinese patent medicine, acupuncture, massage), epidural block]. This paper intends to provide reference for professionals in different medical institutions in the assessment and selection of treatment methods for LBP in China.